The combination of ATR-FTIR and chemometrics for rapid analysis of essential oil from Myrtaceae plants – A review - Islamudin Ahmad, Jihan Azmi Nur Fikri, Ayun Erwina Arifianti, Sarini Abdullah, Abdul Munim (Journal of Applied Pharmaceutical Science, 2022)
Essential oils are widely used in a variety of industries, including food, chemicals, cosmetics, and pharmaceuticals. Like all commercial products, essential oils must pass a stringent quality control procedure established by the industry. Unfortunately, quality control of essential oils has become a difficult task due to the content of biosynthetic conditions and their complexity. The Myrtaceae family is the most well-known essential oil-producing plant in the community. The plants of the Myrtaceae family used for medical and commercial purposes include myrtle, guava, cloves, Eucalyptus, and tea tree, which consists of 140 genera and about 3,500–5,800 species that are scattered in tropical and subtropical areas. Essential oils obtained from this family, Eucalyptus, Melaleuca, Syzygium, and Eugenia, can be rapidly analyzed using Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) and chemometrics. This review article aims to investigate the role and use of ATR-FTIR and chemometric methods as a rapid analysis for essential oils from Myrtaceae plants. The literature search was conducted and accomplished from January to October 2021 using an electronic database such as Scopus, PubMed, Web of Science, Directory Open Access Journal, and Google Scholar. This narrative review highlights various pieces of literature on FTIR, ATR-FTIR, chemometrics, analysis of essential oils, essential oils from Myrtaceae, application of ATR-FTIR, and chemometrics in essential oil from Myrtaceae plants and their prospects.
Keywords: Essential oil, Myrtaceae, ATR-FTIR spectroscopy, chemometrics, quality control.